Strategi Penanaman Karakter Islami Pada Siswa MTS Swasta Al Manar Medan Johor (Studi Kasus Selama Pembelajaran Daring) - Nona Kumala Sari Kumala Sari; Mira Sallini Hutabarat; Erni Susanti; M Sopyan (Al-Ulum: Jurnal Pendidikan Islam, 2020)
It is very important to instill Islamic character in students, because with it students will become human beings with moral and noble character. However, as has happened now, the Covid-19 pandemic has disrupted the conventional learning process. So we need a solution to answer these problems. Specifically, this study aims to analyze: (1) Overview of online learning private MTS Al Manar Medan Johor, (2) Variety of negative characters that appear during the learning period in the midst of the Covid-19 pandemic, (3) Strategies for planting Islamic characters at MTS Al Manar Medan . This research uses qualitative research methods, based on descriptive studies, with research data sources namely teachers, parents, and students. The data collection technique is done by means of observation, interview, and documentation study. The results of the study indicate that online-based learning during the Covid-19 pandemic at MTS Al Manar Medan was carried out in collaboration with the Medan City Minister of Religion in the field of education, namely by using the E-Learning Application. With this application each teacher can enter learning material and at the same time can monitor students whether they have attended attendance. Various negative characters appear during online-based learning, such as cheating or dishonest characters, shy characters, and lazy characters. The strategy carried out in cultivating Islamic character is by giving advice, habituation, modeling, and giving rewards and punishments. Keywords: Islamic character, online learning, educating